Pengaruh Bio-slurry Padat dan Pupuk NPK Tablet Terhadap Pertumbuhan dan Hasil Tanaman Jagung Manis (Zea mays saccharata Sturt) - Ricky Saputra Sinaga; Nelvia Nelvia; Fetmi Silvina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This research aims to look at the interaction effect of bio-slurry giving solid and NPK fertilizer tablets, as well as to stroke the best dose of bio-slurry solid manure and NPK tablet to increase the growth and production of sweet corn. improve (Zea mays Saccharata Sturt). The research was conducted at the test farm, Faculty of Agriculture, University of Riau, Campus Bina Widya, New Simpang Village, District Handsome, Pekanbaru. The study was conducted in September-November 2017. The study consisted of two factors. The first factor is a fixed dose of Bio-Slurry consisting of three levels, namely B0: 0 kg per plot, B1: 7.5 kg per plot and B2: 15 kg per plot. The second factor talet NPK (10:10:14) consists of three levels, namely P0: 0 tablets per plant, P1: 2 tablets per plant and P2: 4 tablets per plant. Of the two factors above 9, treatment combinations were obtained and each was repeated three times, resulting in 27 graphs of experimental units. Data obtained from observations were statistically analyzed using SAS System Version 9.20. The results of the multiplication analysis were continued with Duncan's multiple-range test at 5% level. The observed parameters were plant height, time of male flower, time of female flower, flask diameter, length of tuna, harvest age and cob weight without clot per sample. Increasing doses of bio-slurry solids and NPK tablet improve plant growth and high production, while male flowers, while female flowers, corn cob diameter, corn cob length, corn cob weight and age of the sweet corn crop. Giving solid biological slurry of 15 kg per plot and NPK 100 tablets per plot yields the best growth and production of sweet corn plants. Keywords: Sweet corn, bio-slurry, fertilizer NPK tablet